847 PREOPERATIVE BRAIN MRI/CT FOR PATIENTS WITH POTENTIALLY RESECTABLE ESOPHAGEAL SQUAMOUS CELL CANCER, TO BE OR NOT TO BE ROUTINELY?. (17th September 2021) - Wei, Xiufeng; Li, Yin; Qin, Jianjun; Chen, Xiankai; Zhang, Ruixiang; Kang, Xiaozheng; Xie, Hounai; Xu, Lei; Yang, Yafan
Abstract:  : There are few prospective studies of brain metastasis from esophageal squamous cell cancer (ESCC). The aim of this study was to investigate the necessity of the brain MRI/CT in the preoperative workup for patients with potentially resectable (cT1-4aN0-3) esophageal squamous cell cancer. Methods: This was a prospective cross-section clinical trial (ChiCTR1800020304). There were a total of 468 patients who were diagnosed ESCC from October 2018 to August 2020. Of these 468 patients, 385 patients with cT1-4aN0-3 who were potentially candidates for surgical resection were consecutively enrolled into the study. Preoperative brain MRI/CT was performed preoperatively. The treatment regimen could be changed if the brain metastasis was confirmed. The primary endpoint was the incidence rate of the treatment regimen being changed because of brain metastasis. Results: In all 385 patients, there are only 4 (1%) patients changed their treatment regimen because of brain metastasis proved by MRI/CT. The rate of positive brain MRI/CT findings is 1%. The MRI/CT diagnostic performance for brain metastasis was as follows: sensitivity, 100%; specificity, 100%; positive predictive value, 100%; negative predictive value, 100% and accuracy, 100%. There were no significant difference of bone metastasis among the Age, Sex, Tumor location and clinical stage. Conclusion: Preoperative brain MRI/CT might help identify brain metastases in patients with esophageal cancer, but we do not recommend the brain MRI/CT in the preoperative workup for patients with potentially resectable esophageal squamous cell cancer.